Strategy in theory; strategy in practice. Issue 2 (23rd February 2019) - Strachan, Hew
ABSTRACT: The practice of strategy is different from strategic theory. The latter was largely developed by professional soldiers from the experiences of the Napoleonic Wars, and compared the present with the past to establish general truths about war. It used history as its dominant discipline until 1945. The advent of nuclear weapons made history seem less relevant, and prompted the inclusion of other disciplines; deterrence theory also made strategic theory more abstract and distant from the practice of war. Since 9/11, the experience of war has forced strategy to become less theoretical and to do better in reconciling theory with practice.